PENGARUH PERTUMBUHAN AKTIVA PRODUKTIF DAN DANA PIHAK KETIGA PADA KINERJA OPERASIONAL LEMBAGA PERKREDITAN DESA DI KABUPATEN BADUNG - NILA KRISNA DEWI, PUTU; SUARTANA, I WAYAN (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 4 No 2 (2009))
The aim of this research is to have insight about the effect of earningsassets growth (credit offered) and third parties’ fund (saving and deposits) onLPDs, operational performance (BOPO ratio) in Badung regency bothsimultaneously and partially. Sample is collected using random sampling methodwith total sample of 30 LPDs.This research uses annual data in the period of 2002-2007. Data areanalyzed using multiple linier regressions. The results show that simultaneouslyall independent variables, which consist of growth of credit offered, saving, anddeposits, has significant effect on operational performance of LPDs in BadungRegency during the period of 2003-2007 with adjusted R2 of 0.049. Although,partially only growth of credit offered affects LPDs’ operational performancesignificantly with degree of confidence of 95%.
Keywords: earnings assets growth, third parties’ fund growth, operational performance (BOPO ratio)